Peningkatan Kemampuan Pemahaman dan Motivasi Siswa SMP melalui Model Missouri Mathematics Project (MMP) dengan Menggunakan Game Matematika Online - Andriani Andriani; M. Ikhsan; Bansu Irianto Ansari (Universitas Syiah Kuala, 2016)
This research was aimed to know: (1) the difference of the increasing of understanding mathematical ability who get the learning process through MMP model by using online math game and students who get the learning process conventionally; (2) the difference of the increasing of students motivation who get the learning process through MMP model by using online math game and students who get the learning process conventionally; (3) the interaction between learning model by the level of students on their mathematics increasing of understanding mathematical ability; (4) the interaction between learning model by the students level on the students motivation increasing. This research used quantitative approach by quasi experiment method. The populations were all students of grade VII SMA Arun-LhokseumaweAceh which consisted of five classes. As the sample were taken randomly namely class VII-C as experiment class and class VII-B as controlled class. The research instrument was the ability of mathematics understanding in essay form, motivation questioner of students and observation sheets. Data were analyzed by t-test and Anova. The analysis with result show indicated that (1) the increasing of the students understanding mathematical ability taught through MMP teaching model by using online math game was better than those who were taught conventionally; (2) the increasing of motivation whichs taught through MMP teaching model by using online math game was better than those who were taught conventionally; (3) there was no interaction between learning model by students level on students mathematic of understanding mathematical ability; (4) there was an interaction between learning model by students level on the increasing of the students motivation.